History of bariatric surgery and COVID‐19 outcomes in patients with type 2 diabetes: Results from the CORONADO study. Issue 3 (9th February 2022) - Blanchard, Claire; Perennec, Tanguy; Smati, Sarra; Tramunt, Blandine; Guyomarch, Béatrice; Bigot‐Corbel, Edith; Bordier, Lyse; Borot, Sophie; Bourron, Olivier; Caussy, Cyrielle; Coffin‐Boutreux, Christine; Dutour, Anne; et al.
Abstract: Objective: This study assessed the impact of a history of metabolic and bariatric surgery (MBS) on the clinical outcomes in patients with type 2 diabetes (T2D) and severe obesity hospitalized for COVID‐19. Methods: In this post hoc analysis from the nationwide observational CORONADO (Coronavirus SARS‐CoV2 and Diabetes Outcomes) study, patients with T2D and a history of MBS were matched with patients without MBS for age, sex, and BMI either at the time of MBS or on admission for COVID‐19. The composite primary outcome (CPO) combined invasive mechanical ventilation and/or death within 7 and 28 days following admission. Results: Out of 2, 398 CORONADO participants, 20 had a history of MBS. When matching for BMI at the time of MBS and after adjustment for diabetes duration, the CPO occurred less frequently within 7 days (3 vs. 17 events, OR: 0.15 [0.01 to 0.94], p = 0.03) and 28 days (3 vs. 19 events, OR: 0.11 [0.01 to 0.71], p = 0.02) in patients with MBS ( n = 16) vs. controls ( n = 44). There was no difference in CPO rate between patients with MBS and controls when matching for BMI on admission. Conclusions: These data are reassuring regarding COVID‐19 prognosis in patients with diabetes and a history of MBS compared with those without MBS.